2017
DOI: 10.1371/journal.pone.0187302
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting interaction specificity reveals neuronal and adipocyte Munc18 membrane fusion regulatory proteins differ in their binding interactions with partner SNARE Syntaxins

Abstract: The efficient delivery of cellular cargo relies on the fusion of cargo-carrying vesicles with the correct membrane at the correct time. These spatiotemporal fusion events occur when SNARE proteins on the vesicle interact with cognate SNARE proteins on the target membrane. Regulatory Munc18 proteins are thought to contribute to SNARE interaction specificity through interaction with the SNARE protein Syntaxin. Neuronal Munc18a interacts with Syntaxin1 but not Syntaxin4, and adipocyte Munc18c interacts with Synta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The specific mechanisms involved in the promotion of SG activation by Munc13 have not been fully elucidated. Studies in neuronal cells have indicated that Munc13 may promote the depolymerization of syntaxin-Munc18 complexes and maintain the stability of syntaxin, which may promote the combination of VAMP and SNAP25 (23,(29)(30)(31)(32). Previously, syntaxin2 was demonstrated to be localized in human airway goblet cells and was implicated in regulating mucin SG exocytosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms involved in the promotion of SG activation by Munc13 have not been fully elucidated. Studies in neuronal cells have indicated that Munc13 may promote the depolymerization of syntaxin-Munc18 complexes and maintain the stability of syntaxin, which may promote the combination of VAMP and SNAP25 (23,(29)(30)(31)(32). Previously, syntaxin2 was demonstrated to be localized in human airway goblet cells and was implicated in regulating mucin SG exocytosis (33).…”
Section: Discussionmentioning
confidence: 99%